MUSICAL ANALYSIS OF THE "SMOKE EFFECT": SIALANG RAYO RITUALS AND FOREST FIRES AS A SOURCE OF MUSICAL CREATION - Indra Gunawan; Muhammad Taufik Hidayat (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2022)
In Indonesian society, especially western Indonesia. The tradition that was created was not to interpret something imaginary such as art or other social activities but community actions in developing business in the field of plantations. One of the consequences of this forest fire is the loss of a community ritual tradition in taking honey bee debt. This tradition is known as the Sialang Rayo ritual. Sialang Rayo Ritual is now rarely found in the life of the people of Bungo regency. The results of the composer's research then developed into a musical composition entitled "Smoke Effect." Music composition III part is a reflection and imagination of the artist who is concerned with seeing the loss of one of the characters of the surrounding community life. In this article, the author analyzes how the artist processes the musicological elements of the Sialang Rayo ritual into an experimental musical composition. The use of Western musical techniques became the basis for the processing and development of this musical composition.Keywords: ritual Sialang Rayo; Smoke Effect; analysis musicABSTRAKKebakaran hutan saat ini menjadi semacam sebuah tradisi pada masyarakat indonesia, khusus indonesia bagian barat. Tradisi yang diciptakan bukan untuk mengiterpretasikan sesuatu imajinasi seperti hal nya kesenian maupun kegiatan sosial lainnya melainkan tindakan masyarakat dalam mengembangkan usaha dibidang perkebunan. Salah satu akibat dari kebakaran hutan ini yaitu hilangnya suatu tradisi ritual masyarakat dalam mengabil madu lebah hutang. Tradisi ini dikenal dengan nama ritual Sialang Rayo. Ritual Sialang Rayo kini sangat jarang di temukan pada kehidupan masyarakat daerah kabupaten Bungo. Dari hasil penelitian yang dilakukan oleh Indra Gunawan (pengkarya), kemudian dikembangkan kedalam komposisi musik 3 bagian yang berjudul “Smoke Effect”. Karya ini merupakan refleksi dan imajinasi pengkarya yang prihatin melihat hilangnya sebuah salah satu karakter kehidupan masyarakat disekitarnya. Pada artikel ini penulis menganalisis bagaimana pengkarya mengolah unsur-unsur musikologi dari ritual Sialang Rayo kedalam sebuah komposisi musik eksperimental. Penggunaan teknik musik musik barat menjadi dasar pengolahan dan pengembangan pada komposisi musik ini.Kata kunci: Ritual Sialang Rayo; Smoke Effect; Analisis Musik